KUSHTHA VYADHI - AAHARAJ HETU ADHYAYANA - Deepali Subhash Pisal; Sunil.R.Pandhare. (International Journal of Applied Ayurved Research, 2016)
Ayurveda is science of life which is magical effect in all disease since ancient era to present scenario.its still test to the time.In Ayurveda,all skin disorder can include under the heading of ‘kushta’.Sometimes its difficult to find out cause of kushta. In other medical sciences there is minimum availability of cause and treatment of each vyadhi. Ayurveda gives details of panchalakshana nidana. Knowledge of panchanidana is very important to diagnosis of any kind of disease. If hetu of disease is found then line of treatment can be decided easily.Hetu can be Aharaj, viharaj and Mansik. Through this paper we have made an attempt to re-evaluate the relation between kushta-vyadhi and its Aaharaj hetu.